2019
DOI: 10.3390/nu11102375
|View full text |Cite
|
Sign up to set email alerts
|

The Gut Microbiota in Celiac Disease and probiotics

Abstract: Celiac disease (CeD) is an immune-mediated enteropathy, and unique in that the specific trigger is known: gluten. The current mainstay of therapy is a gluten-free diet (GFD). As novel therapies are being developed, complementary strategies are also being studied, such as modulation of the gut microbiome. The gut microbiota is involved in the initiation and perpetuation of intestinal inflammation in several chronic diseases. Intestinal dysbiosis has been reported in CeD patients, untreated or treated with GFD, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(76 citation statements)
references
References 118 publications
2
53
1
3
Order By: Relevance
“…There is a growing body of evidence that exposure to gliadin induces an increased zonulin release which determines the opening of the tight junctions, thereby affecting intestinal barrier integrity. This, in turn, enhances the inflammatory response that contributes to CD pathogenesis and disease progression [165,166].…”
Section: Can Fecal Mirnas Be Celiac Disease Biomarkers Interacting Wimentioning
confidence: 99%
See 1 more Smart Citation
“…There is a growing body of evidence that exposure to gliadin induces an increased zonulin release which determines the opening of the tight junctions, thereby affecting intestinal barrier integrity. This, in turn, enhances the inflammatory response that contributes to CD pathogenesis and disease progression [165,166].…”
Section: Can Fecal Mirnas Be Celiac Disease Biomarkers Interacting Wimentioning
confidence: 99%
“…and Leuconostoc compared to the normal population [163,175,[177][178][179][180][181][182][183][184][185]. The overall composition and dynamic of gut microbiota in CD patients were reviewed elsewhere [165,[173][174][175][176]185,186]. Although there are ecological differences in the upper and lower part of the intestinal tract that influence the microbiota composition, the bacterial signatures detected in biopsies and feces of CD patients were found to be correlated [179,188].…”
Section: Can Fecal Mirnas Be Celiac Disease Biomarkers Interacting Wimentioning
confidence: 99%
“…They are able to modulate intestinal barrier function and contribute to the development of protective/tolerogenic immune response (96,97). The correlation between CD and intestinal dysbiosis has been described by several groups (98)(99)(100). Indeed, gut microbiota has been shown to contribute to CD pathogenesis by (1) controlling the digestion of gluten peptides therefore generating toxic and tolerogenic peptides (99,101,102); (2) modulating the intestinal permeability (45,(102)(103)(104); (3) driving the proper formation and differentiation of mucosal epithelium (99,105); (4) regulating the expression of pro-inflammatory or anti-inflammatory cytokines (99,106).…”
Section: Probioticsmentioning
confidence: 99%
“…Various chronic disorders such as inflammatory bowel disease [13], and type 1 diabetes [14] have been shown to be associated with alterations in the gut microbial composition. Recent studies have also suggested that intestinal dysbiosis may play a role in the pathogenesis of coeliac disease [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%